Five Wrist Operations That Give the Best Results. Issue 2 (25th January 2021) - Maldonado, Andres A.; Pulos, Nicholas; Rhee, Peter C.; Shin, Alexander Y.
Abstract : Learning Objectives: After reading this article and viewing the videos, the participant should be able to: 1. Recognize the following five wrist operations as consistent options for different wrist injuries: carpal tunnel release, medial femoral condyle bone flap for scaphoid nonunion associated with carpal collapse and avascular necrosis, scaphocapitate arthrodesis for Kienböck disease, percutaneous screw fixation of nondisplaced scaphoid fracture, and four-corner arthrodesis. 2. Know the state-of-the-art of these five procedures. 3. State the indications of each operation. 4. List the surgical steps of these five procedures. Summary: The wrist is a complex joint that concentrates different types of tissues (e.g., bone, cartilage, ligaments, nerves, vessels) and a broad different spectrum of diseases. Treatment of wrist injuries has improved during recent years, mainly because of improvement in strategy, techniques, microsurgical equipment, understanding anatomy and improvements in technology. In this article, we present the five operations (i.e., carpal tunnel release, medial femoral condyle bone flap for scaphoid nonunion associated with carpal collapse and avascular necrosis, scaphocapitate arthrodesis for Kienböck disease, percutaneous screw fixation of nondisplaced scaphoid fracture, and four-corner arthrodesis) that have consistently given good outcomes in patients suffering from different wrist injuries/maladies.